The Effect of Using Owl Houses on Reducing Rattus Argentiventer and Its Impact on Increasing Rice Production - Nurjanah Nurjanah; Gita Aditya Sach; Wachdijono Wachdijono (Journal of World Science, 2025)
Effective and sustainable control of rat pests is a major challenge in rice cultivation. An increasingly friendly method is the use of owl houses (Tyto alba) as a biological agent to control rat populations. This study examines the effect of owl houses on reducing rat pests and their impact on increasing rice production in Linggajati Village, Arahan District, Indramayu Regency, West Java Province, Indonesia. Primary data were collected from March to June 2025 and analyzed in July 2025. Quantitative methods included direct field observations, rat population analysis before and after owl house installation, and crop yield measurements. The sample consisted of 112 rice farmers who installed owl houses around their fields, using simple random samplings. Data was analyzed with Structural Equation Modeling (SEM) via the AMOS application. Results indicated full mediation: owl houses directly reduced rat pest attacks (0.97), which positively impacted rice production (0.89). The most dominant factor in the owl house variable was the number of owls settling there (1.03), and pest reduction in areas without owl houses showed a very positive effect (1.75). The study found that the presence of owls can reduce rat populations by up to 70%, leading to an average 20% increase in rice production compared to fields without owl houses. These findings demonstrate that owl houses offer an effective ecological solution to support sustainable rice agriculture.